Makna Journaling bagi Generasi Z - Tia Habibah Dwitami; Ratri Rizki Kusumalestari (Bandung Conference Series: Journalism, 2023)
Abstract. As Generation Z is accustomed to living with digital technology and social media, there is an unique phenomenon called journaling among them. Journaling is a new term popular among Generation Z to refer to writing activities such as diaries. This research on "The Meaning of Journaling for Generation Z" aims to find out the motives and experiences, typifications and meanings of Generation Z in journaling. Using a qualitative research method with Alfred Schutz's phenomenological study approach. In-depth interviews, audio recordings and documents were conducted as data collection techniques and analyzed using phenomenological reduction data analysis techniques. To test the validity of the data, source triangulation was used. Abstrak. Di tengah Generasi Z yang terbiasa hidup dengan teknologi serba digital dan sosial media, terdapat fenomena unik yang disebut dengan journaling di kalangan ini. Journaling merupakan istilah baru yang populer di kalangan Generasi Z untuk menyebut kegiatan menulis seperti halnya pada buku harian. Penelitian tentang “Makna Journaling bagi Generasi Z” ini bertujuan untuk mengetahui motif dan pengalaman, tipifikasi serta makna Generasi Z dalam melakukan journaling. Menggunakan metode penelitian kualitatif dengan pendekatan studi fenomenologi Alfred Schutz. Wawancara mendalamdan rekaman audio dilakukan sebagai teknik pengumpulkan data dan menganalisisnya menggunakan teknik analisis data reduksi fenomenologi. Terakhir, untuk menguji keabsahan data digunakan triangulasi sumber.